Silicon and Plant–Animal Interactions: Towards an Evolutionary Framework - Katz, Ofir (Plants (Basel), 2020)
Herbivory is fundamental in ecology, being a major driver of ecosystem structure and functioning. Plant Si and phytoliths play a significant antiherbivory role, the understanding of which and of its evolutionary context will increase our understanding of this phenomenon, its origins, and its significance for past, extant, and future ecosystems. To achieve this goal, we need a superdisciplinary evolutionary framework connecting the role of Si in plant–herbivore interactions, in global processes, and in plant and herbivore evolution. To do this properly, we should acknowledge and incorporate into our work some basic facts that are too often overlooked. First, there is great taxonomic variance both in plant Si contents, forms, and roles, but also in herbivore responses, dietary preferences, and in fossil evidence. Second, species and their traits, as well as whole ecosystems, should be seen in the context of their entire evolutionary history and may therefore reflect not only adaptations to extant selective factors but also anachronistic traits. Third, evolutionary history and evolutionary transitions are complex, resulting in true and apparent asynchronisms. Fourth, evolution and ecology are multiscalar, in which various phenomena and processes act at various scales. Taking these issues into consideration will improve our ability to develop this needed theoretical framework and will bring us closer to gaining a more complete understanding of one of the most exciting and elusive phenomena in plant biology and ecology.